Host Plant and Thermal Stress Induce Supernumerary Instars in Caterpillars. Issue 1 (23rd November 2019) - Abarca, Mariana; Lill, John T; Weiss, Martha R
Abstract: Environmental stressors may induce variation in the number of larval instars of holometabolous insects. Host plant quality and ambient temperature can both induce this life history shift in the silver-spotted skipper, Epargyreus clarus (Cramer 1775) (Lepidoptera: Hesperiidae). To better understand this phenomenon, we raised larvae on high-quality (kudzu) or low-quality (wisteria) host plants in growth chambers under three temperature regimes (20, 26, and 32°C) that were either constant or diurnally fluctuating ( T ± 5°C), and recorded survival and incidence of supernumerary instars. Larvae feeding on the low-quality host and/or experiencing thermal stress were more likely to show supernumerary development (SD). A subset of treatments yielded a mix of SD and TD (typical development) individuals, allowing for comparisons between phenotypes. Under the most stressful treatment (20 ± 5°C, wisteria), development time was 9 days longer in SD than in TD individuals; by contrast, at typical summer temperatures (26 ± 5°C), also on wisteria, total development time did not differ between these two phenotypes. Head capsules of both second and third instars were smaller in SD individuals. A retrospective logistic regression analysis indicated that third-instar head capsule size could be used to predict expression of the SD phenotype. By the ultimate instar, however, there were no detectable differences in head capsule size, and SD and TD individuals did not differ in pupal mass, strongly suggesting that the SD phenotype functions as a compensatory mechanism allowing E. clarus larvae to achieve the same size at metamorphosis (a strong fitness correlate) as TD larvae.